2013
DOI: 10.1155/2013/969026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Size and Pretreatment Methods on Germination of Albizia lebbeck

Abstract: Albizia lebbeck is a multipurpose tree species prioritised for conservation in Malawi. The different plant parts are used in traditional medicine to treat different diseases. However, the seeds are dormant, and the tree species remain undomesticated. A study was conducted to evaluate the effect of seed size and presowing on the germination of Albizia lebbeck in a nursery. Seeds were grouped into four categories in regard to their length, small (≤0.5 cm), medium ( cm), large (≥0.8 cm), and mixture of small, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 8 publications
(11 reference statements)
5
20
0
2
Order By: Relevance
“…The results in the present study are in agreement with [18] which reported that seed size did not have an effect on germination percentage of Pinus roxburghii seedlings. A similar result was also reported by [19,20] on Virola koschny and Albizia lebbeck, respectively. However, the findings of the present study do not agree with the findings of [21] cited by [22] which reported that germination percentage was strongly influenced by seed size of loblolly pine (Pinus taeda), such that germination percentage difference was reported to be considerable between large, medium, and small seed.…”
Section: Germination Performancesupporting
confidence: 91%
“…The results in the present study are in agreement with [18] which reported that seed size did not have an effect on germination percentage of Pinus roxburghii seedlings. A similar result was also reported by [19,20] on Virola koschny and Albizia lebbeck, respectively. However, the findings of the present study do not agree with the findings of [21] cited by [22] which reported that germination percentage was strongly influenced by seed size of loblolly pine (Pinus taeda), such that germination percentage difference was reported to be considerable between large, medium, and small seed.…”
Section: Germination Performancesupporting
confidence: 91%
“…Therefore these must be considered in afforestation and reforestation projects. Trees such as Albizialebbeck, Faidherbiaalbida, Acacia polycantha and Senna siamea or Cassia Siameaare recommended for reforestation in many areas worldwide as well as in Malawi especially in riparian system and in agroforestry programmes because they have multipurpose characteristics, provide quick benefit to the ecosystem and human, and have no or little negative ecological effect on the riparian system [16]- [18]. However the information on the initial establishment and growth rates of these trees species in Malawian conditions is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Trees such as Albizia lebbeck, Faidherbia albida, Acacia polyacantha, and Senna siamea or Cassia siamea are recommended for reforestation in many areas worldwide as well as in Malawi, especially in riparian systems and in agroforestry programmes because they have multipurpose characteristics, provide quick benefit to the ecosystem and human, and have no or little negative ecological effect on the riparian system [5], [6], [7]. However, the information on the initial establishment and growth rates of these tree species in Malawian conditions is not available but in Karnataka, India, a height increment of 2.5 m per year of S. siamea has been recorded, and in 3 years in West Bengal, trees were almost 8 m tall with a stem girth of 25 cm [8].…”
Section: Introductionmentioning
confidence: 99%